Journalism in history, history in journalism: A historiographical critique of the newspaper as a source material for research - Marvin R. Soriano (International Review of Social Sciences Research, 2025)
This historiographical critique explores the dual function of newspapers as both historical records and active agents in shaping historical narratives. It interrogates the value and limitations of newspapers as source material in historical research, emphasizing their potential to provide rich, contemporaneous insights into past events, while also cautioning against their inherent biases and ideological underpinnings. Drawing from media theory and critical historiography, the paper employs an interdisciplinary methodology that includes content and comparative analysis of literature from media studies, journalism, and history. This approach uncovers how newspapers reflect societal norms, power structures, and political agendas, thereby shaping not only public opinion but also historical interpretation. The study highlights the methodological challenges in using newspapers as sources, such as editorial bias, selective reporting, and the political economy of print media. Despite these challenges, the paper demonstrates that newspapers, when critically examined and contextually grounded, can serve as valuable and corroborative materials for understanding historical processes. It underscores the importance of treating newspapers not merely as passive channels of information but as dynamic texts that both mirror and mold historical consciousness. Ultimately, the study advocates for a critical and reflexive engagement with newspapers in historiographical work, proposing that with careful analysis and triangulation with other sources, newspapers can enhance the depth and nuance of historical inquiry. By situating newspapers within their broader cultural and political contexts, researchers can better appreciate their role in both documenting and constructing the past, thus affirming their relevance and reliability in historical scholarship.